"Peleia" luso-castelhana e os efeitos de sentidos em o linguajar do gaúcho brasileiro de Dante de Laytano - Camani, Emanuele Bitencourt Neves (2012)
This paper results from a research study on the organization of historiographic discourse regarding ethnic and socio-historical formation of the southern inhabitants of the south of Brazil, identified as brazilian gaucho, reflecting on his language or manner of speech that combines elements of Portuguese and Spanish. Having as the corpus of research the work of Dante Laytano, entitled O Linguajar do Gaúcho Brasileiro, published in 1981, the research wanted to identify the treatment given by this author to the two areas of study: language and historiography which established his point of view about representation of the source of the gaucho language, from the sources consulted and referenced in the work above. To achieve the proposed objective and answer the questions that guiding the research, we sought, in the concepts of the Event Semantics and Discourse Analysis (AD) the basement that made possible to analyze and reflect on how the elements of language operated in historiography texts on the language feature of the brazilian gaucho which is called linguajar by the author above. With the light of the AD, becomes evident in this work a discourse about this linguajar, that is in circulation and still redefines the social history of the gaucho and producing effects of meaning, when establish a linguajar for him. The Event Semantics allowed the analysis of the relationship between the question of designation and interdiscourse of enunciatively sequences (SEs) identified, in this work, that rewriting the linguajar of the brazilian gaucho, and also seeks to highlight their regularities and/or conflicts. The study shows that: a) O Linguajar do Gaúcho Brasileiro (1981) seeks to reference the lusitanian matrix of the gaucho language, in other words, to reaffirm their identity, which is brazilian, b) in this work, the author shows that discursive memory is signified by the memorable discourse of portuguese language, establishing relations of conflict with the spanish language (espanholismos), silencing the meanings attributed to the regional and local, in search of the unity of the portuguese language, but in this case, can be considered as a brazilian language, constitutive of the identity of the gaucho and his linguajar. Due to the importance of language for communication, identity, integration and unity of the citizens of the same country or between countries, as the case of the brazilian gaucho, it is understood that this research could lead to further study to this designation, as that, on the one hand, this approach extends the analysis possibilities of the name and sources as historiographical resources from the perspective of the Event Semantics; on the other hand, studies on interdiscourse issues, from the semantic functioning.